Pulse Dose Methylprednisolone Therapy for Adult Idiopathic Inflammatory Myopathy. (July 2015) - Raghu, Padmanabhan; Manadan, Augustine M.; Schmukler, Juan; Mathur, Tanisha; Block, Joel A.
Abstract : Idiopathic inflammatory myopathies (IIM) are a rare group of autoimmune diseases characterized by muscle inflammation. Typically high-dose daily oral corticosteroids are used as the first-line therapy of IIM. Pulse dose intravenous methylprednisolone (IVMP) has been used for serious or refractory cases. Here, we systematically analyze the therapeutic effect of pulse dose IVMP in patients with IIM in a large municipal safety net medical center and review the literature on pulse IVMP in adult IIM. We conducted a retrospective chart review of patients who were diagnosed with IIM in the rheumatology clinics of the Cook County Health and Hospital Systems. Data collected included patient demographics, diagnosis, immunosuppressive therapies, serial serum creatine kinase (CK) measurements, and serial muscle strength testing. Seven patients received pulse dose IVMP for active myositis. At the time of pulse dose IVMP, the mean strength in the weakest muscle group was rated as 3.1 of 5 (range, 2–4; SD, 0.9) and the mean peak CK was 5746 U/L (range, 1602–14, 039; SD, 4911). Dysphagia was reported in 5 of the 7 patients at the time of IVMP. Four to six weeks after IVMP, the mean strength in the weakest muscle group was 3.3 of 5 (range, 1–5; SD, 1.5) and mean peak CK was 1064 U/L (range, 63–1788, SD, 712). Four to six weeks after IVMP, dysphagia had resolved in 2 and improved in 3. At the end of follow-up, mean strength in the weakest muscle group was 4.7 of 5 (range, 4–5; SD, 0.5), mean peak CK was 480 U/L (range, 37–1016; SD, 337), and the mean prednisone dosage was 15 mg (range, 2.5–60; SD, 21). Although our study has certain limitations, our cohort of adult patients with IIM had marked improvement in clinical and biochemical outcomes. Four to six weeks after IVMP infusion, there was a rapid improvement in muscle enzyme levels, muscle strength, and dysphagia. This therapy warrants further controlled trials.